Bartonella species in fleas from Palestinian territories: Prevalence and genetic diversity. Issue 2 (December 2014) - Nasereddin, A.; Risheq, A.; Harrus, S.; Azmi, K.; Ereqat, S.; Baneth, G.; Salant, H.; Mumcuoglu, K.Y.; Abdeen, Z.
ABSTRACT Bartonellosis is an infectious bacterial disease. The prevalence and genetic characteristics of Bartonella spp. in fleas of wild and domestic animals from Palestinian territories are described. Flea samples (n=289) were collected from 121 cats, 135 dogs, 26 hyraxes and seven rats from northern (n=165), central (n=113), and southern Palestinian territories (n=11). The prevalent flea species were: Ctenocephalides felis (n=119/289; 41.2%), Ctenocephalides canis (n=159/289; 55%), and Xenopsylla sp. (n=7/289; 2.4%). Targeting the Intergenic Transcribed Spacer (ITS) locus, DNA of Bartonella was detected in 22% (64/289) of all fleas. Fifty percent of the C. felis and 57% of the Xenopsylla sp. contained Bartonella DNA. DNA sequencing showed the presence of Bartonella clarridgeiae (50%), Bartonella henselae (27%), and Bartonella koehlerae (3%) in C. felis. Xenopsylla sp. collected from Rattus rattus rats were infected with Bartonella tribocorum, Bartonella elizabethae, and Bartonella rochalimae. Phylogenetic sequence analysis using the 16S ribosomal RNA gene obtained four genetic clusters, B. henselae and B. koehlerae as subcluster 1, B. clarridgeiae as cluster 2, while the rat Bartonella species (B. tribocorum and B. elizabethae) were an outgroup cluster. These findings showed the important role of cat and rat fleas as vectors of zoonotic Bartonella species in Palestinian territories. It is hoped that this publication will raise awareness among physicians, veterinarians, and other health workers of the high prevalence of Bartonella spp. in fleas in Palestinian territories and the potential risk of these pathogens to humans and animals in this region.